Improving Students' Numeracy Literacy at Ujung Tebu Elementary School through the Use of Simple Mathematics (Addition and Multiplication) as a Learning Media: Meningkatkan Literasi Numerasi Siswa Di SDN Ujung Tebu Melalui Penggunaan Math Simple (Addition and Multiplication) Sebagai Media Pembelajaran - Huswatun Hasanah; Fitri Aida Sari; Melinda Yanuar; Maulfi K. Abadi; Firdaus (JATI EMAS (Jurnal Aplikasi Teknik dan Pengabdian Masyarakat), 2024)
Numeracy literacy skills are very important in encouraging developments in the field of science and technology and increasing individual competitiveness in Indonesia. The PISA test results show that the abilities of Indonesian students are low. Developing literacy habits consistently will have a major impact on improving the overall quality of human resources. Individuals who have a strong understanding of literacy will play an important role in fostering an interactive academic atmosphere. The main aim of this program is to help students, especially at SDN Ujung Tebu, to improve their numeracy skills, especially multiplication. This can also improve students' numeracy literacy skills. By using learning media, Simple Math (Addition and Multiplication) for the learning process, can be seen the students become more enthusiastic about being involved in learning activities so that they can improve students' numeracy literacy skills. In addition, it can improve critical thinking skills and work well together.